Insight Into the Microbial Co-occurrence and Diversity of 73 Grapevine (Vitis vinifera) Crown Galls Collected Across the Northern Hemisphere - Gan, Han Ming; Szegedi, Ernõ; Fersi, Rabeb; Chebil, Samir; Kovács, László; Kawaguchi, Akira; Hudson, André O.; Burr, Thomas J.; Savka, Michael A. (Frontiers in Microbiology, 2019)
Crown gall (CG) is a globally distributed and economically important disease of grapevine and other important crop plants. The causal agent of CG is Agrobacterium or Allorhizobium strains that harbor a tumor-inducing plasmid (pTi). The microbial community within the CG tumor has not been widely elucidated and it is not known if certain members of this microbial community promote or inhibit CG. This study investigated the microbiotas of grapevine CG tumor tissues from seven infected vineyards located in Hungary, Japan, Tunisia, and the USA. Heavy co-amplification of grapevine chloroplast and mitochondrial ribosomal RNA genes was observed with the widely used Illumina V3-V4 16S rRNA gene primers, requiring the design of a new reverse primer to enrich for bacterial 16S rRNA from CG tumors. The operational taxonomic unit (OTU) clustering approach is not suitable for CG microbiota analysis as it collapsed several ecologically distinct Agrobacterium species into a single OTU due to low interspecies genetic divergence. The crown gall microbial community assemblages were significantly different across sampling sites (ANOSIM global R = 0.63, p-value = 0.001) with evidence of site-specific differentially abundant ASVs. The presence of Allorhizobium vitis in the CG microbiota is almost always accompanied by Xanthomonas and Novosphingobium, the latter may promote the spread of pTi plasmid by way of acyl-homoserine lactone signal production, whereas the former may take advantage of the presence of substrates associated with plant cell wall growth and repair. The technical and biological insights gained from this study will contribute to the understanding of complex interaction between the grapevine and its microbial community and may facilitate better management of crown gall disease in the future.